Dampak Presidential Threshold terhadap Hasil Pemilihan Presiden pada Rangkaian Acara Pemilu Menurut Pandangan Mahasiswa - Saputra, Febrian Vivaldi; Vadira, Annisa Bela; Marshall Jericho Gerard; Melyana Barnesa; Radityo, Henry Anand Septian; Matthew Mahendra; Ahmad Nadil; Farchan Martha Adji Chandra; Okalani, Raden Sjora; Hanggara, Fariz Putra (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2023)
. Presidential elections in Indonesia use a presidential threshold to limit the number of election candidates. This policy affects the voters and the democracy in Indonesia. This article, The Effect of the Presidential Threshold System towards The Result of Presidential Election from Undergraduate Students Perspective, was written to understand the effects of the presidential threshold from the perspective of students. This article formulates how the presidential threshold affects the people of Indonesia as voters, how the presidential threshold affects polarization towards certain political parties, and how the presidential threshold affects democracy in Indonesia. A questionnaire is used to collect the data, of which will be described qualitatively. The result is that the presidential threshold does limit the number of presidential candidates and could polarize voters towards a political party. This is caused by the presidential threshold system itself that limits the number of candidates and political parties that could lead voters' attitude while voting.